Unintended Consequences of Food Subsidies : The Case of the Haiti Rice Subsidy - Arias, Diego; Carneus, Maxime (World Bank, Washington, DC, 2014)
Haiti is an important rice consumer, and a big rice importer. Around 86 percent of the Haitian population consumes rice. The decision to implement an indirect subsidy was made based on the fact that import prices had in the past been transmitted fully and immediately to rice consumers. Thus, a subsidy to the price of rice at the level of the importers was expected to be passed on immediately into benefits (savings) to rice consumers. The Government also prohibited rice exports to the Dominican Republic in order to avoid re-export of subsidized rice. The subsidy scheme was implemented by forming a public-private sector Presidential Commission between the Central Bank of Haiti (BRH), the President's Office and rice importers. Although the rice price subsidy program did produce the intended savings to Haitian consumers during the 4-month period of the subsidy program (April-August 2008), this intervention caused medium term distortions in the domestic market of imported rice such that domestic prices of imported rice have risen beyond the price that consumers would have faced without a subsidy program. The actual prices consumers faced after the subsidy program was implemented were much more volatile than the estimated price without a subsidy program, pointing to also an increased consumer uncertainty about local market prices for rice. Using a targeted food voucher as a subsidy mechanism is not only more efficient, but can have higher impact on nutrition as it can be used for a wide variety.